2015
DOI: 10.1371/journal.pone.0142474
|View full text |Cite
|
Sign up to set email alerts
|

What Would Jaws Do? The Tyranny of Film and the Relationship between Gaze and Higher-Level Narrative Film Comprehension

Abstract: What is the relationship between film viewers’ eye movements and their film comprehension? Typical Hollywood movies induce strong attentional synchrony—most viewers look at the same things at the same time. Thus, we asked whether film viewers’ eye movements would differ based on their understanding—the mental model hypothesis—or whether any such differences would be overwhelmed by viewers’ attentional synchrony—the tyranny of film hypothesis. To investigate this question, we manipulated the presence/absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
142
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(162 citation statements)
references
References 61 publications
(96 reference statements)
11
142
0
Order By: Relevance
“…It seems that emotional words in printed media have similar function to emotional faces in visual media. Furthermore, filmmakers are skilled in their ability to direct attention toward such important social cues (Loschky et al, 2015; Cutting and Armstrong, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…It seems that emotional words in printed media have similar function to emotional faces in visual media. Furthermore, filmmakers are skilled in their ability to direct attention toward such important social cues (Loschky et al, 2015; Cutting and Armstrong, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…This is as opposed to a volitional top-down process. Our own prior studies have shown only weak effects of the viewer's event model on their attentional selection in the domain of viewing film clips (Hutson, Smith, Magliano, & Loschky, 2017;Loschky, Larson, Magliano, & Smith, 2015). Thus, our goal in this study is to better understand the processes involved in generating bridging inferences in visual narratives involving eye movements and, in doing so, test a novel hypothesis from SPECT.…”
Section: Study Overviewmentioning
confidence: 94%
“…Of the remaining 62, a subset of 36 males were chosen to match the ASD group, based on gender, age, IQ and motion. Mean age for the matched TD group was 20.8 (range [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. For the eye movement analyses, three participants from the ASD group and two from the TD group were excluded for failing to achieve adequate calibration on the eye tracker.…”
Section: Participantsmentioning
confidence: 99%
“…This creates a movie experience which is robustly shared across viewers, with previous studies describing widespread correlations in neural responses across individuals, extending well beyond perceptual regions into social processing areas, among others 14 . This attentional synchrony however, seems to be dominated by transient visual and social cues, and is only very weakly modulated by higher level comprehension of the narrative, or inferences based on the mental states of the characters in the scene, as is demonstrated by studies which manipulated comprehension through temporal shuffling of scenes 15 , or manipulation of available context 16,17 .…”
Section: Introductionmentioning
confidence: 99%